The thread of life - Wollheim, Richard (Cambridge, Massachusetts Harvard university press, 1984)
This book is based on the William James Lectures delivered at Harvard University in 1982. It offers a new approach to the philosophical understanding of a person, taking as fundamental the process of living as a person, and emphasising the continuity and development across time of an individual life.